2020
DOI: 10.18502/ijph.v49i10.4703
|View full text |Cite
|
Sign up to set email alerts
|

Population Attributable Risk of Hyperuricemia in Hypertension Incidence in 20-74-Year-Old Population during a 10-Year Longitudinal Cohort: Yazd Healthy Heart Cohort

Abstract: Background: The population attributable risk (PAR) percent has used widely in public health policy. We aimed to calculate the attribute risk of hypertension due to hyperuricemia by Levin's formulas compare to direct PAR calculation method. Methods: This was a sub-study of Yazd Healthy Heart Cohort (YHHC). Overall, 1256 normotensive individuals were enrolled through multistage randomized cluster sampling and followed up for mean 9.8 years, from 2005-2015. The threshold cutoff point of the hyperuricemia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research on the correlation between hyperuricemia and hypertension has a history of more than a century. There is increasing evidence that hyperuricemia is an independent risk factor for hypertension 31 . A prospective cohort of 539 patients aged 12–17 years with type 2 diabetes also confirmed that high UA increased the risk of hypertension in adolescents 32 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Research on the correlation between hyperuricemia and hypertension has a history of more than a century. There is increasing evidence that hyperuricemia is an independent risk factor for hypertension 31 . A prospective cohort of 539 patients aged 12–17 years with type 2 diabetes also confirmed that high UA increased the risk of hypertension in adolescents 32 .…”
Section: Discussionmentioning
confidence: 73%
“…There is increasing evidence that hyperuricemia is an independent risk factor for hypertension. 31 A prospective cohort of 539 patients aged 12-17 years with type 2 diabetes also confirmed that high UA increased the risk of hypertension in adolescents. 32 A Japanese cohort study involving 3584 adult patients with prehypertension found that the cumulative incidence of hypertension progression within 5 years in hyperuricemic patients was significantly higher than that in non-hyperuricemia patients.…”
Section: Discussionmentioning
confidence: 75%
“…According to the JNC7 Guideline, hypertension is de ned as a systolic blood pressure ≥ 140, or a diastolic blood pressure ≥ 90, or taking antihypertensive drugs(28). We measured the blood pressure of our participants using a mercury sphygmomanometer in phase one and a digital sphygmomanometer, Omron Model, Japan in recent years (27,29,30).…”
Section: Evaluating the Incidence Of Hypertensionmentioning
confidence: 99%